Optimalisasi Perlindungan Animal Welfare Right Dalam Kebun Binatang Dari Eksploitasi Sirkus Hewan Sebagai Upaya Mewujudkan Ekokrasi - Juanita Bil Atia; Ira Rahayu Ningsih; Wahyu Indra Triyadi; Ledy Zahra Rezeky (UIN Syarif Hidayatullah Jakarta, 2026)
The zoo is an area that has the main function as a conservation institution to preserve animal diversity amidst the threat of extinction. In practice, conservation efforts at zoos are problematic because based on investigative findings that around 90% of zoos are uninhabitable and it is exacerbated by the phenomenon of circus animal attractions. Based on these problems, writers conducted this research to identify cases of protection of animal welfare rights in zoos due to norms that have not provided legal certainty so that they are used for animal exploitation. As for the research method that used is normative juridical with statute approach, case approach, and conceptual approach. The results of this research show that there are still conservation institutions, especially garden animals, which use animals as objects of exploitation through the enchantment of animal circuses to gain unilateral benefits. In fact, animal circus attractions are a form of improper treatment of animals which violates the ethics of animal welfare and the green constitution which is the fundamental value of animals as part of the environment. Therefore, it is necessary to revise and make the legal substance effective regarding protected wild animal attractions with the core of the policy focusing more on considering ecocracy-based animal welfare values, as well as prohibiting animal attractions that have fatal consequences for animals used as circus objects.